Defense Policy Strategy based on Network Centric Warfare (NCW) toward Asymmetric Threats: Case study from an Indonesian Perspective - Putra, Nengah; Kukuh Susilo, April (JOIN (Jurnal Online Informatika), 2026)
Implementation of NCW as a core element of defense policy requires a comprehensive strategic framework. Without these basic elements, NCW may remain underutilized or fail to deliver the desired results in the face of asymmetric threats. Therefore, it is important to explore a Network Centric Warfare (NCW)-based defense strategy in addressing asymmetric threats. This paper seeks to analyze the formulation of a defense policy strategy based on the principles of Network Centric Warfare (NCW) to effectively address asymmetric threats by exploring the theoretical foundations of NCW in Indonesia Perspective. The analysis of NCW implementation strategies focuses on information superiority, communication speed, and cross-unit coordination as strategic solutions for detecting and responding to non-linear attack patterns. NCW-based defense strategies require inter-sectoral synergy as part of a holistic national security approach. Given the nature of asymmetric threats, which often involve non-state actors and span multiple domains (physical, digital, social), collaboration between the Indonesian National Armed Forces (TNI), the Indonesian National Police (Polri), the National Cyber and Cryptography Agency (BSSN), the State Intelligence Agency (BIN), and government and private institutions is crucial. NCW provides a technological framework and systems that can integrate these various actors into a national defense strategy that is responsive, adaptive, and collaborative in addressing the complexity of contemporary threats. The primary contribution of this paper is to formulate a defense policy strategy based on Network-Centric Warfare (NCW) principles, which is not only important for assessing NCW in the naval domain but also has potential application in a joint, interagency environment in Indonesia.